Vascular complications in adults and pediatrics live-donor renal transplantation: 3 decades of single centre experience - Shokeir, Ahmed; Hassan, Nabil; Kamal, Mohamed; Soliman, Shady; Ghoneim, MA (African Journal of Nephrology, 2009)
We analyzed the incidence of vascular complications in adults and pediatrics live donor renal transplantations over 3 decades and compared its impact upon patient and graft survival in both groups. Material and methods: Between March 1976 and December 2005, 1785 live-donor renal transplantswere performed in a single institute, of the 1546 adults and 239 pediatric (age ≤18 years). The incidence of different types of vascular complications were determined in both groups. Long term patient and graft survival in patients with or without vascular complications and in various types of vascular complications were calculated & compared in both groups. Results: The overall incidence of vascular complications was 2.9%, it was equally 2.9% in both groups. In adults, 46 complications in 45 patients included 16 arterial, 10 renal artery thrombosis (0.6%), 2 cases of spasm in renal artery(0.1%), renal artery stenosis in 5 (0.3%), renal vein thrombosis in one (0.06%) and hemorrhagic complications in 28 patients whereas there were no thrombotic complications in the pediatric group, 6 case of hemorrhage (2.5%) and one case of renal artery stenosis (0.4%). There is steady decrease of vascular complications over the last 3 decades. The vascular complications significantly adverse patient and graft survival in both groups (p<0.001). The 5-years patient and graft survival in adults and pediatrics with or without vascular complications were 59.5 ± 9.2%, 89.14 ± 0.89%, 57.5 ± 18.7% and 90.18 ± 2.2% for the patient and 40.14 ± 7.75%, 97.79 ± 1.14%, 28.57 ± 17.07% and 77.18 ± 3.02% for the graft. There is no statistical significant difference in either patient or graft survival in thrombotic, stenotic or hemorrhagic complications in adult or hemorrhagic complications in the pediatric group (p=0.22 and p=0.142 respectively). Conclusions: There is no increase in incidence of vascular complications in pediatrics than adult transplants. The survival either graft or patient is comparable between adult and pediatric with or without vascular complications and the subgroups of vascular complications.